المناخ التنظٌمًي وأثره على سلوك العاملٌين دراسة مٌيدانٌية مدٌيرٌية سونلغاز لولاية الاغواط - بن موسى جهاد; بن موسى سمٌية; بن عون بودالي (My University, 2022)
The goal of this study is to try to know the systemic climate and its effects on the behavior of workers in SONALGAZ in the city of Laghouat and it also aims to analyze the systemic climate of SONALGAZ in all ways possible, Ecofriendllnyes, The community, and the over-all systemic climate of said group of workers in one-system meaning “Culture, Tradition, Community rules, Behaviors and doings, Community Beliefs”. The different ways of working that effect the activities and manners of behavior and humanitarian and economical effects inside the organization and the trying to know the behavior of individual workers into Its internal and external dimensions And the adjustment process ;feelings ; humanitarian directione ;Feelings;strees of work;the needs of humanitarian and Physiological and Community; Frustration; Conflict ; The competition..). Data were collected through a questionnaire consisting of 20 questionson on 90 wrokor(male ; female)on the Enterprise Of these, 80 were studyable questionnaires Of the total population of the study: 1- There is a positive effect of the organizational climate on the behavioral outcomes of the workers in this entrprise in laghout. 2- There is a statistical indication between the organizational climate and the behavior of the personnel working in Sonelgazل 3- There is a price to develop the organizational climate in an organization to positively impact an individual's behaviorل